2017
DOI: 10.1638/2016-0063r.1
|View full text |Cite
|
Sign up to set email alerts
|

EPIDEMIOLOGIC EVALUATION OF ELEPHANT ENDOTHELIOTROPIC HERPESVIRUS 3B INFECTION IN AN AFRICAN ELEPHANT (LOXODONTA AFRICANA)

Abstract: This epidemiologic study follows a 5-yr-old male African elephant ( Loxodonta africana ) during an episode of hemorrhagic disease (HD) due to elephant endotheliotropic herpesvirus 3B (EEHV3B) utilizing data from complete blood counts, electrophoresis and acute phase protein analysis, and polymerase chain reaction (PCR) of multiple body fluids during and after the clinical episode. The elephant presented with sudden onset of marked lethargy and inappetence followed by hypersalivation, hyperemia of the conjuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 17 publications
0
33
0
Order By: Relevance
“…Importantly, zoo elephant research has repeatedly identified differences between African and Asian elephants. Different drugdosage requirements (Bechert et al, 2008), reproductive pathologies Brown et al, 2016), digestive physiologies (Dierenfeld, 2006;van Sonsbeek et al, 2013), pheromones (Rasmussen & Schulte, 1998) and susceptibility to EEHV (Bronson, E., et al, 2017) are a few such examples. Nonetheless, African and Asian elephants have typically been viewed and managed collectively as 'elephants' in captive settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, zoo elephant research has repeatedly identified differences between African and Asian elephants. Different drugdosage requirements (Bechert et al, 2008), reproductive pathologies Brown et al, 2016), digestive physiologies (Dierenfeld, 2006;van Sonsbeek et al, 2013), pheromones (Rasmussen & Schulte, 1998) and susceptibility to EEHV (Bronson, E., et al, 2017) are a few such examples. Nonetheless, African and Asian elephants have typically been viewed and managed collectively as 'elephants' in captive settings.…”
Section: Discussionmentioning
confidence: 99%
“…Provisionally, EEHV types 1A, 1B, 4 and 5 appear to be endemic within Asian elephants, with EEHV1A and 1B being associated with the majority of lethal cases, and the other EEHV types within African elephants (Long et al ., ). At the time of writing, EEHV‐HD has been recognized most often in Asian elephants, but a few cases have also been observed in African elephants (Richman et al ., , ; Latimer et al ., ; Bronson, E., et al ., ).…”
Section: Diseasesmentioning
confidence: 99%
“…Furthermore, the relatively rapid response of the acute-phase response makes measuring APP concentrations useful for identifying sub-clinical disease before clinical signs are manifested [ 12 ]. APPs have been measured in a variety of wildlife species in recent years, including Asian [ 14 , 15 , 16 ] and a single African elephant [ 17 ] to assess the response to pathologies such as elephant endotheliotropic herpesvirus (EEHV), pododermatitis, trauma, and infection. In elephants, serum amyloid A (SAA) is considered to be a major APP, increasing rapidly in response to acute inflammation, whereas haptoglobin (HP) responds more moderately and may be reflective of more chronic inflammation [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several health problems affect elephants both in situ and ex situ that could benefit from a better understanding of underlying disease processes and improved tools for detection and monitoring. Elephant endotheliotropic herpesvirus hemorrhagic disease (EEHV HD) affects almost one in four Asian elephant calves born in zoos globally [ 28 ], as well as African elephants [ 17 , 29 , 30 ], and in captive and wild populations in Asia [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. One proposed hypothesis for the severity of EEHV HD could be that immunologically naïve calves fail to mount an effective immune response to keep up with viral replication [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…EEHV2, -3, -6, and -7 are recognized as endemic in African elephants (1), but to date, hemorrhagic disease caused by these viruses has not been documented to the same extent as for EEHVs in Asian elephants. Recently, however, lethal (J. Proudfoot and M. Fayette, unpublished data) and nonlethal (5) cases of EEHV3 infection have been observed, raising increased concern over EEHV-HD in these elephants, as well. Among Asian elephants, juveniles between the ages of 2 and 8 years appear to be most vulnerable to EEHV-HD (1).…”
mentioning
confidence: 99%